Métodos diagnósticos de xeroderma pigmentoso - Sánchez Cadena, Anahí Melissa (2025)
Xeroderma Pigmentosum is a genetic disorder that can affect both the skin and the neurological system due to even minimal exposure to ultraviolet (UV) radiation. Early diagnosis is therefore essential for the timely treatment of the disease. The objective of this study was to describe and analyze the clinical and functional methods employed in the diagnosis of Xeroderma Pigmentosum, assessing their implementation within the Ecuadorian medical context to enhance diagnostic capacity and comprehensive clinical management of patients. Methods: This was a qualitative study based on a bibliographic review, using a cross-sectional, non-experimental design with descriptive and explanatory scope. The literature search was conducted through major digital databases such as PubMed, Elsevier, among others, using Medical Subject Headings (MeSH) terms. Results: The most commonly used diagnostic methods were histopathological analyses, DNA repair assays, and molecular genetic tests. These methods serve as complementary tools to confirm the clinical manifestations of Xeroderma Pigmentosum. Conclusion: Genetic diagnostic methods are essential to confirm the genotype of Xeroderma Pigmentosum in affected patients. When combined with clinical findings, they support effective counseling and timely therapeutic intervention.